Power system stabilizer design for ideal AVR using local measurements. (August 2023) - Kumari, Rajni; Kumar, Ajit
Abstract: In this work, the application of an Ideal automatic voltage regulator is presented for an interconnected power system. The Ideal AVR is designed using the feedback linearization technique and it is shown that the voltage regulation response with the Ideal AVR is superior to conventional linear AVR. Subsequently, a power system stabilizer is added to improve the small signal stability. The proposed control scheme is demonstrated to provide vastly superior voltage regulation and damping of the rotor mode compared to conventional control. Simulation results are presented using a sub-transient (6th order) model of the IEEE 14 generator 59 bus system. Highlights: An Ideal AVR based on the feedback linearization technique is designed for a multi-machine power system using local measurements. Plant signal up to the secondary bus of the step-up transformer is utilized. The proposed AVR demonstrates a significantly improved response when compared to the linear AVR. Subsequently, a PSS is added to enhance overall system stability and is compared with both linear AVR and PSS control schemes. Lastly, it is noted that designing a PSS with a ideal AVR is straightforward and robust.